Pengembangan Media Pembelajaran Menggunakan Scribus pada Materi Karya Fiksi - Zahra Firlia; Ansori Ansori (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Learning media must be developed into various types because there are limitations in the use and selection of appropriate media for learning. This study aims to produce learning media products using Scribus based on works of fiction in class VIII at SMP Negeri 4 Palembang. This research is a development study utilizing a modification of the ADDIE and Alessi & Trollip models. The stages of this research are analysis, design, and development. The data collected in this study comprises both quantitative data, in the form of questionnaires, and qualitative data, in the form of interviews. The results of the learner needs analysis are 80.51% (very high need), and the teacher needs analysis is 69.64% (need). Then, the results of media validation achieve a percentage of 96.92% (very feasible), the results of material validation accomplish a percentage of 83.07% (also very possible), and the results of language validation achieve a rate of 89.09% (also very feasible). From the results of this study, it can be concluded that the learning media developed fall into a very feasible category and can be used for teaching and learning activities on works of fiction.